Singapore Country Assistance to Help Extinguish Forest Fire in South Sumatera - Anton Minardi; Taufik Taufik; Dewi Astuti; Mochammad Irvan Pamungkas (Program Pascasarjana Universitas Sriwijaya, 2020)
Forest and land fires has become one of the most difficult natural disaster to handle, forest and land fires happened every year all around the world, and become one of the many cause of global warming and climate change and if it is not resolved immediately then it will harm all of the living beings on this earth. Forest and land fire in Indonesia happened nearly every year, the first biggest forest and land fires ever recorded in Indonesia happened in 1998-1999 which harm many parties, especially the ASEAN, since then, forest and land fires in Indonesia nearly happened every year whose impact neighboring countries like Singapore and Malaysia, In 2015 forest and land fires can be said quite large and once again affects neighboring countries, until Indonesia neighboring countries like Singapore want to try to help extinguish the forest and land fires in Indonesia.